2019
DOI: 10.1108/nfs-12-2018-0352
|View full text |Cite
|
Sign up to set email alerts
|

Effect of kiwifruit juice and tumbling on tenderness and lipid oxidation in chicken nuggets

Abstract: Purpose The purpose of this study was to study the effect of kiwifruit juice and tumbling in improving tenderness and to access antioxidant potential of kiwifruit juice. Design/methodology/approach Three treatment groups were made: Spent hen meat was subjected to still marination (SM) and tumbling marination (TM). This meat was used for preparation of whole muscle chicken nuggets and compared with control (without marination) nuggets (Con). These treatments were subjected to analysis of physicochemical chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 42 publications
3
2
0
Order By: Relevance
“…It is also clear that pH value, TVBN and TBA values increased with increasing the storage period as such effects were more pronounced in the control untreated spent hen patties (Tables 2, 3, and 4). Similar to the obtained results, Pooona et al (2019) observed a significant reduction in TBA of spent hen meat nuggets treated with kiwi which is related to its antioxidant properties. Moreover, Abdel-Wahab et al ( 2020) found that kiwi reduces lipid and protein oxidation of the marinated fish and they attributed this effect to its content of bioactive compounds which have great antioxidant activity.…”
Section: Deterioration Criteriasupporting
confidence: 89%
See 3 more Smart Citations
“…It is also clear that pH value, TVBN and TBA values increased with increasing the storage period as such effects were more pronounced in the control untreated spent hen patties (Tables 2, 3, and 4). Similar to the obtained results, Pooona et al (2019) observed a significant reduction in TBA of spent hen meat nuggets treated with kiwi which is related to its antioxidant properties. Moreover, Abdel-Wahab et al ( 2020) found that kiwi reduces lipid and protein oxidation of the marinated fish and they attributed this effect to its content of bioactive compounds which have great antioxidant activity.…”
Section: Deterioration Criteriasupporting
confidence: 89%
“…Similar results were recorded by Pooona et al (2019), who observed a significant increase in protein and moisture content, and a significant reduction in fat content with a non-significant reduction in ash content in spent hen nuggets treated with kiwi. However, AL-Hameed and AL-Jawary (2017) noticed that treatment of spent hen thigh meat with kiwi juice significantly increased moisture content and significantly decreased protein, and fat as compared with the control treatment.…”
Section: Proximate Chemical Analysissupporting
confidence: 88%
See 2 more Smart Citations
“…Additionally, the injection of spent hen meat with kiwi fruit enzyme (10%) improved its juiciness and tenderness, as well as overall acceptability [ 36 ]. In another study, Pooona et al [ 37 ] obtained an enhancement in flavor, texture juiciness, and overall acceptability of spent hen chicken nuggets marinated with kiwi fruit juice. In the same regard, improvement of the sensory attributes of spent hen chicken emulsion incorporated with kiwi peel extract (2.5%) during storage at 4 °C for 9 days was reported by Singh et al [ 35 ].…”
Section: Resultsmentioning
confidence: 99%